The origins of love and hate : a constructive and original criticism of freudian psychology as it concerns infancy, sociability, love and sublimation - Suttie, Ian D. (Mitcham (Australia) : Penguin Books, 1960)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/02/016 Archief Roger Vertongen
Engels
Monografie